J.D. Salinger - American Writers 51 : University of Minnesota Pamphlets on American Writers - Jr., James E. Miller (Book collections on Project MUSE., 1966)
J.D. Salinger - American Writers 51 was first published in 1965. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.